Additive Effect of Physical Activity and Sedentary Time on Depressive Symptoms in Rural Japanese Adults: A Cross-Sectional Study - Abe, Takafumi (J Epidemiol, 2019)
BACKGROUND: Previous studies have reported an additive effect of moderate-to-vigorous physical activity (MVPA) and sedentary time (ST) on depressive symptoms. However, no studies have been conducted in rural community settings. This cross-sectional study investigated whether the additive effect of MVPA and ST was associated with depressive symptoms in rural Japanese adults. METHODS: We identified 2,814 participants from health examinations conducted in Shimane, rural Japan, in 2012 and analyzed data from 1,958 participants. We assessed depressive symptoms using the Zung Self-Rating Depression Scale and measured the total time spent on MVPA and ST using a Japanese short version of the International Physical Activity Questionnaire. Poisson regression analysis examined the prevalence ratios (PR) of depressive symptoms in nine category combinations of MVPA level (no, insufficient, or sufficient MVPA) and ST level (high, moderate, or low ST). RESULTS: A total of 117 (6.0%) participants had depressive symptoms. Compared with the reference category (no MVPA/high ST), multivariate analysis showed that the likelihood of depressive symptoms was significantly lower in the sufficient MVPA/low ST category (PR 0.23; 95% confidence intervals [CI], 0.08–0.66), insufficient MVPA/low ST category (PR 0.37; 95% CI, 0.16–0.86), and insufficient MVPA/moderate ST category (PR 0.39; 95% CI, 0.17–0.90). CONCLUSION: Analysis of the additive effect of MVPA and ST showed that the combinational category of sufficient MVPA and low ST had the lowest prevalence of depressive symptoms in rural Japanese adults. Moderate ST and low ST showed significantly lower likelihoods of depressive symptoms, regardless of insufficient MVPA.